The Effect of Repetitive Transcranial Magnetic Stimulation of Cerebellar Swallowing Cortex on Brain Neural Activities: A Resting-State fMRI Study - Dong, Linghui; Ma, Wenshuai; Wang, Qiang; Pan, Xiaona; Wang, Yuyang; Han, Chao; Meng, Pingping (Frontiers in Human Neuroscience, 2022)
Objective: The effects and possible mechanisms of cerebellar high-frequency repetitive transcranial magnetic stimulation (rTMS) on swallowing-related neural networks were studied using resting state functional magnetic resonance imaging (rs-fMRI). Method: A total of twenty-three healthy volunteers were recruited, and nineteen healthy volunteers were finally included for statistical analysis. Before stimulation, the cerebellar hemisphere dominant for swallowing was determined by single pulse TMS. The cerebellar representation of the suprahyoid muscles of this hemisphere was selected as the target for stimulation with 10 Hz rTMS, 100% resting motor threshold (rMT) and 250 pulses, with every 1s of stimulation followed by an interval of 9s. The motor evoked potential (MEP) amplitude of the suprahyoid muscles in bilateral cerebral cortex was measured before and after stimulation to evaluate the cortical excitability. Forty-eight hours after elution, rTMS was reapplied on the dominant cerebellar representation of the suprahyoid muscles with the same stimulation parameters. Rs-fMRI was performed before and after stimulation to observe the changes in amplitude of low frequency fluctuation (ALFF) and regional homology (ReHo) at 0.01–0.08 Hz, 0.01–0.027 Hz, and 0.027–0.073 Hz. Results: After cerebellar high-frequency rTMS, MEP recorded from swallowing-related bilateral cerebral cortex was increased. The results of rs-fMRI showed that at 0.01–0.08 Hz, ALFF was increased at the pons, right cerebellum and medulla and decreased at the left temporal lobe, and ReHo was decreased at the left insular lobe, right temporal lobe and corpus callosum. At 0.01–0.027 Hz, ALFF was decreased at the left temporal lobe, and ReHo was decreased at the right temporal lobe, left putamen and left supplementary motor area. Conclusion: rTMS of the swallowing cortex in the dominant cerebellar hemisphere increased the bilateral cerebral swallowing cortex excitability and enhanced pontine, bulbar, and cerebellar spontaneous neural activity, suggesting that unilateral high-frequency stimulation of the cerebellum can excite both brainstem and cortical swallowing centers. These findings all provide favorable support for the application of cerebellar rTMS in the clinical practice.